2006
DOI: 10.1017/s0022215106002155
|View full text |Cite
|
Sign up to set email alerts
|

Familial systemic amyloidosis associated with bilateral sensorineural hearing loss and bilateral facial palsies

Abstract: The Finnish type of familial amyloid polyneuropathy due to variant gelsolin is a rare form of familial amyloidosis. The subtype was first described in 1969 and is characterized by progressive cranial neuropathies, corneal lattice dystrophy and distal sensorimotor dysfunction. It is extremely uncommon, with only two families known to be affected in the UK. We discuss the case of a 70-year-old woman who presented with bilateral facial nerve palsies, bilateral sensorineural hearing loss and Finnish type familial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…1,12,[24][25][26] Reported neurological symptoms include bilateral progressive facial paralysis, impaired hearing, upper and lower limb paresthesiae, decrease in touch and vibration sensation, carpal tunnel syndrome, and ataxia and motor weakness with age. 11,25,27,28 Functional disturbances of the central nervous system may manifest as mild cognitive impairment. 29 Many patients show signs of mild renal or cardiac amyloidosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,12,[24][25][26] Reported neurological symptoms include bilateral progressive facial paralysis, impaired hearing, upper and lower limb paresthesiae, decrease in touch and vibration sensation, carpal tunnel syndrome, and ataxia and motor weakness with age. 11,25,27,28 Functional disturbances of the central nervous system may manifest as mild cognitive impairment. 29 Many patients show signs of mild renal or cardiac amyloidosis.…”
mentioning
confidence: 99%
“…GA typically manifests after age 30, initially with ophthalmological symptoms . Reported neurological symptoms include bilateral progressive facial paralysis, impaired hearing, upper and lower limb paresthesiae, decrease in touch and vibration sensation, carpal tunnel syndrome, and ataxia and motor weakness with age . Functional disturbances of the central nervous system may manifest as mild cognitive impairment .…”
mentioning
confidence: 99%
“…Singh-Grewal et al presented two patients with FMF coexisting with MEFV and CIAS1 mutations and suffering from progressive SNHL [18] . Also, Hornigold et al [19] presented bilateral SNHL in a patient with familial systemic amyloidosis. All of these could be accepted as rare presentations.…”
Section: Discussionmentioning
confidence: 99%
“…Cochlea may be one of the organs that might possibly be affected by systemic amyloidosis. Hornigold et al [15] reported a case of 70 year old female patient with familial systemic amyloidosis and bilateral sensorineural hearing loss. Although still controversial, many Table 2 The type and number of mutations in the FMF patients.…”
Section: Discussionmentioning
confidence: 99%